ANALYSIS OF THE BUDGET SURPLUS (SiLPA) IN THE ACEH REVENUE AND EXPENDITURE BUDGET - Agustina; Azlina; Mirnawati; Lisnawati; Yudiansyah Shaleh (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2026)
A form of accountability from the regional government for all implementation of programs and activities is by producing a calculation of the Regional Revenue and Expenditure Budget (APBD). Remaining Budget Estimates (SiLPA) is part of financing receipts to cover a deficit or to utilize a surplus. This research aims to determine SiLPA and the aspects that cause SiLPA. This research uses secondary data, namely documents obtained from the Directorate General of Financial Balance (DJPK) in the form of the Aceh Revenue and Expenditure Budget (APBA). The analytical method used is quantitative descriptive analysis. The results of the research show that there is a Remaining Budget Calculation (SiLPA) in the APBA during the 2018-2025 period with numbers that fluctuate. A large SiLPA value indicates low commitment and professionalism of public implementing officials. The largest SiLPA value in 2020 was IDR 3,969,617,354,782 followed by 2021, namely IDR 3,933,680,612,390. The lowest SiLPA value can be seen in 2024 at IDR 530,262,155,634 followed by 2021 at IDR 990,987,381,464. If we look at the growth of SiLPA, the largest growth will be in 2025 with a growth rate of 160% or almost 3 times greater than the previous year, namely 2024. Meanwhile, the smallest SiLPA growth will be in 2022 with a growth rate of -67% smaller than the previous year, namely 2021. The aspect that caused SiLPA to occur in Aceh during the 2018-2025 period was due to the excess of Regional Original Income (PAD) which exceeded the target. PAD that exceeds this target comes from regional taxes, the results of separated regional wealth management and other legitimate sources.